2015
DOI: 10.1073/pnas.1515228112
|View full text |Cite
|
Sign up to set email alerts
|

Unmyelinated type II afferent neurons report cochlear damage

Abstract: In the mammalian cochlea, acoustic information is carried to the brain by the predominant (95%) large-diameter, myelinated type I afferents, each of which is postsynaptic to a single inner hair cell. The remaining thin, unmyelinated type II afferents extend hundreds of microns along the cochlear duct to contact many outer hair cells. Despite this extensive arbor, type II afferents are weakly activated by outer hair cell transmitter release and are insensitive to sound. Intriguingly, type II afferents remain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
111
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 44 publications
13
111
1
Order By: Relevance
“…This strongly supports the idea that type II SGNs, but not type I SGNs, can serve a role in pain sensation within the auditory system. A second study by Liu et al revealed that the function of type II SGNs in auditory nociception is mediated by extracellular ATP mainly released by SCs after HC damage [80]. In this study, the authors mechanically ablated HCs and detected slow activation of type II SGNs, which was dependent on both ATP-gated P2X receptors and G-protein-coupled P2Y receptors.…”
Section: Newly Emerging Concepts In the Function Of Type II Sgnsmentioning
confidence: 62%
See 2 more Smart Citations
“…This strongly supports the idea that type II SGNs, but not type I SGNs, can serve a role in pain sensation within the auditory system. A second study by Liu et al revealed that the function of type II SGNs in auditory nociception is mediated by extracellular ATP mainly released by SCs after HC damage [80]. In this study, the authors mechanically ablated HCs and detected slow activation of type II SGNs, which was dependent on both ATP-gated P2X receptors and G-protein-coupled P2Y receptors.…”
Section: Newly Emerging Concepts In the Function Of Type II Sgnsmentioning
confidence: 62%
“…Immunostaining studies show that the ATP-gated ion channel P2X 2 is present in the synaptic regions of type I and type II SGNs beneath IHCs and OHCs [78, 79], suggesting that SGNs may respond to extracellular ATP. Application of ATP to dissected cochleae not only depolarizes OHCs and indirectly evokes EPSCs in type II afferents, but also evokes an inward current to depolarize type II afferents [72, 80]. Upon mechanical trauma, ATP is released by damaged HCs, generating intracellular calcium increase and ATP release among surrounding HCs and SCs (Fig.…”
Section: Newly Emerging Concepts In the Function Of Type II Sgnsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 and 8). In light of this developmental timeline, synaptic physiology of type-II terminals obtained from rats at P5-P10 (Liu et al, 2015; Weisz et al, 2014) could differ in significant ways from the mature state.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this extended dendritic arbor, type II afferents are only weakly activated by hair cell glutamate release (Weisz et al 2009;Weisz et al 2012) and are insensitive to sound Robertson 1984;Robertson et al 1999), although they project centrally in parallel with neighboring type I afferents (Berglund and Brown 1994;Brown et al 1988;Brown and Ledwith 1990;Morgan et al 1994). Emerging evidence suggests that type II afferents instead respond to tissue damage (Flores et al 2015;Liu et al 2015) perhaps to serve as cochlear nociceptors. Further insight into type II function will require knowledge of their central connectivity, as well as animal models in which type II function can be altered selectively.…”
Section: Introductionmentioning
confidence: 99%